Archéologie du bâti et anthropologie. L’exemple du technicien dans le Massif central et sur ses marges (xie– xiiie siècles) - David Morel (L'Atelier du CRH)
This study proposes to establish the characteristics of building construction, its organization and its consequences, while referring to the perceptible architectural evolutions in the diocese of Clermont from the end of 11th throughout the 13th century. The ecclesiastical building site focuses these concerns, from the large building sites of Limagne and its vast structures to the more modest sanctuaries of smaller mountains. The analysis is also interested in secular construction, as it allows us to clarify the diversity of techniques and the position of various actors, and to measure the impact of technical knowledge and the environment on the social conditions of the builders. We will also widen the debate by considering the following questions: how a constructed space is structured and appropriated; the affirmation of heritages; and the individuality of the skilled worker.